The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1186/s40359-023-01161-y
|View full text |Cite
|
Sign up to set email alerts
|

Stigma towards people with tuberculosis: a cross-cultural adaptation and validation of a scale in Indonesia

Abstract: Introduction Tuberculosis (TB) remains a highly stigmatised disease that can cause or exacerbate mental health disorders. Despite increased awareness of the importance of reducing TB stigma, validated tools to measure TB stigma remain scarce. This study aimed to culturally adapt and validate the Van Rie TB Stigma Scale in Indonesia, a country with the second largest TB incidence worldwide. Methods We validated the scale in three phases: translation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…10 Using various methods to estimate TB Stigma, 6 many studies have found that a substantial proportion of people with TB experience diverse forms of TB Stigma including enacted (experiences of being excluded, isolated, and/or discriminated against), anticipated (having perception, expectation, and/or fear of being stigmatized), or self (loss of self-esteem, loss of dignity, fear and/or shame) stigma. [11][12][13] In our previous study with more than 600 people with TB in Indonesia, we described that not only did 61% of people with TB experience moderate TB stigma but that such a stigma was also associated with depression and reduced QoL. 7 People with TB in our study also identi ed a substantial unmet need for peer support.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…10 Using various methods to estimate TB Stigma, 6 many studies have found that a substantial proportion of people with TB experience diverse forms of TB Stigma including enacted (experiences of being excluded, isolated, and/or discriminated against), anticipated (having perception, expectation, and/or fear of being stigmatized), or self (loss of self-esteem, loss of dignity, fear and/or shame) stigma. [11][12][13] In our previous study with more than 600 people with TB in Indonesia, we described that not only did 61% of people with TB experience moderate TB stigma but that such a stigma was also associated with depression and reduced QoL. 7 People with TB in our study also identi ed a substantial unmet need for peer support.…”
Section: Introductionmentioning
confidence: 73%
“…Firstly, individual counseling by either healthcare workers or research team member applied at the rst healthcare visit following TB diagnosis. At this point, the baseline status of people with TB's TB stigma levels, mental health, and quality of life will also be evaluated using tools validated in the Indonesian setting 7,12 and a verbal and written invitation to a group psychological counseling will be provided. Secondly, a monthly community-based group counseling will be held in an agreed communal space distinct from healthcare facilities and led by TB survivors.…”
Section: Delphi Surveymentioning
confidence: 99%
“…Additionally, other versions of the TSS factor loadings were 0.52–0.80. 28 , 50 , 51 However, there is currently no available report on the factor loadings of the original Chinese version of the scale. Therefore, the high correlation coefficients between the adapted TSS and its factors also indicate the high internal consistency of the scale.…”
Section: Discussionmentioning
confidence: 99%
“…This study also found that the adapted TSS was categorized into two dimensions after conducting EFA, and the EFA of the Indonesian version of the TSS supported a two-factor model, but with a slightly different division of items, which may be due to the different cultural backgrounds in different regions. 28 , 52 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation